Performance of Silica Gel as Moisture Removal from Mortar - Anak Guntor, Nickholas Anting; Lim Meng Siang, Alvin John; Prasetijo, Joewono (International Journal of Sustainable Construction Engineering and Technology, 2020)
Silica gels are widely used as a desiccant to protect the product from moisture damage, which has capacity to absorb moisture from surrounding at level of 100% based on its own weight. Due to this performance, an innovative approach has been taken by applying the silica gel as moisture absorbance from mortar layer. The main objective of this research is to study the performance of silica gel as moisture absorption material that mainly to reduce the surface moisture of tested mortar samples. A series of procedures for experimental work has been designed purposely for this study. Three mortar samples with size of 300mm x 300mm x 50mm were prepared accordingly for each of sample with water-cement ratio of 0.40, 0.45 and 0.50. Initially, mortar samples were ponded with three liters of fresh water for period of 24-hours, and excess water were removed once completed. Then, data of surface moisture of mortar samples together with weight of silica gel was measured and collected simultaneously every 30 minutes for 6 hours. Experimental study found that S3, mortar with w/c of 0.5 had experienced the highest reduction of surface moisture rate of 0.047%/min due to the presence of silica gel. Silica gel, G2 that placed at the mortar with w/c of 0.45 has the highest rate of absorption of 0.119gram/min. When the number of usage increases, the performance of silica gel reduces. Lastly, a relationship is determined that as the surface moisture of tested mortar samples decreases, the weight of silica gel increases. As for the conclusion, selected silica gel showed a potential to be applied as moisture removal material for mortar, which then prevents the growth of mould or fungi.